Management of Peat Fires on Smoldering Phase (Case Study: District Siak and District Kampar Riau Province) - Syafrudin Syafrudin; Haryono S. Huboyo; Bella Nasila D (Waste Technology, 2015)
The difficulty of finding land for farming activities in Indonesia caused some communities began to switch utilizing peat land for agricultural areas such as oil palm. Oil palm plantation is a commodity that has been developed in Indonesia.Oil palm planted area has increased rapidly.Since 1967 extensive oil palm plantations has increased 35times to 5.6 million ha in 2005 and about 7.8 million ha in 2009. The biggest expansion of oil palm plantations occur in 6 province,one of them is Riau.Most people take a practical way to open agricultural areas by burning peat.Riau Province in Indonesia is one of the major hotspots for peat fires during the dry season. Peat fire at smouldering phaseemits a lot of compounds that are not completely oxidized (e.g. CO, VOCs, PAHs) that more dangerous than the emissions released during combustion at flaming fires. Particulate Matter (PM 2.5) is one of the emissions from peat fires too.However, existing data on VOCs and PM 2.5 of smoke from peat fires Indonesia is still limited.The aim of this study was to analyze the concentration of VOCs and PM 2.5 on emissions from peat fires in the Langkai Village Siak District and RimboPanjang Village Kampar District Riau Province when compared with background site and the permissible exposure limit and provide recommendations based on the results of this research.VOCs measurement method is based on NIOSH 1500 and EPA TO-17 while the PM 2.5 based on IMPROVE A method. The average concentration of PM 2.5 is 996.72 ± 531.01μg/m3. PM2.5 concentrations increased (compared with the background site) was very high at 4,838%.This condition causes a decrease in air quality and serious health problems. While the results of the maximum TVOCs concentration obtained in Siak District was 391,880 g/m3, while in Kampar Districtwas 195,940 g/m3. TVOCs concentration atSiak Districtwas 130.63 times greater than the existing quality standards, while at Kampar District regency was 65.31 times.Environmental improvement recommendations based on the results of this research were buffer zone areadesign to reduce air pollution as a result of peat fires and sealing the ditchs to prevent the spread of fires.